On groups with biprimary subgroups of even order - Sokhor, I. (Algebra and Discrete Mathematics, 2017)
We investigate groups in which maximal subgroups of even order are primary or biprimary. We also research soluble groups with restriction on a number of prime devisors of some proper subgroup orders. We give applications of received results to cofactors of proper subgroups.